Rural finance for food security for the poor: implications for research and policy - Zeller, Manfred; Schrieder, Gertrud; von Braun, Joachim; Heidhues, Franz (International Food Policy Research Institute, 1997)
The authors take a fresh look at the role of rural financial policy in improving household food security and alleviating poverty. They develop a conceptual framework for relating access to financial services to food security and review empirical findings on household demand for financial services. They explore the potentials for linking informal lenders (relatives, credit groups, and moneylenders) with the formal financial systems (banks and cooperatives). Then they review the constraints to development of rural financial markets and ways to circumvent these constraints by examining innovative institutions, especially those that include participation by the poor themselves.